Autobiographical memory differences among individuals with subclinical depression and PTSD - Anne, Michele (2021)
Autobiographical memories are complex multidimensional memories an individual has about their past, which are used for bonding, problem solving, creating self-concepts, and emotion regulation. Previous research has found differences in autobiographical memory recall among individuals with clinical levels of depression and post-traumatic stress disorder (PTSD) in comparison to psychological healthy individuals. However, the extent of these differences among individuals with subclinical levels of depression and PTSD, and the mechanisms that may underlie or influence these differences have not been established clearly. These gaps in the knowledge limit our understanding into the type of memory-related difficulties experienced, and whether subclinical samples will likely benefit from similar memory-related interventions as clinical samples.